Human muscle fibre type‐specific regulation of AMPK and downstream targets by exercise. (27th February 2015) - Kristensen, Dorte E.; Albers, Peter H.; Prats, Clara; Baba, Otto; Birk, Jesper B.; Wojtaszewski, Jørgen F. P.
Abstract : Keypoints: AMP‐activated protein kinase (AMPK) is an important regulator of cellular energy status during exercise. Most human studies investigating skeletal muscle protein signalling have been performed in whole muscle biopsy samples, yet recent studies suggest muscle fibre type‐specific AMPK expression with potential fibre type‐specific regulation of AMPK during exercise. This study provides novel and comprehensive data on human muscle fibre type‐specific expression levels of AMPK subunits and downstream targets of AMPK. We show a differentiated response to exercise of key metabolic signalling proteins in human type I and type II muscle fibres during interval exercise, not evident during continuous exercise. These differences between exercise types were not present in whole muscle biopsy samples. Our findings highlight the importance of performing fibre type‐specific measurements and the increased activation of AMPK in interval vs . continuous exercise could be important for exercise type‐specific adaptations, i.e. metabolism, insulin sensitivity and mitochondrial density in human skeletal muscle. Abstract: AMP‐activated protein kinase (AMPK) is a regulator of energy homeostasis during exercise. Studies suggest muscle fibre type‐specific AMPK expression. However, fibre type‐specific regulation of AMPK and downstream targets during exercise has not been demonstrated. We hypothesized that AMPK subunits are expressed in a fibre type‐dependent manner and that fibre type‐specific activation of AMPK and downstream targets is dependent on exercise intensity. Pools of type I and II fibres were prepared from biopsies of vastus lateralis muscle from healthy men before and after two exercise trials: (1) continuous cycling (CON) for 30 min at 69 ± 1% peak rate of O2 consumption ( V ̇ O 2 peak ) or (2) interval cycling (INT) for 30 min with 6 × 1.5 min high‐intensity bouts peaking at 95 ± 2% V ̇ O 2 peak . In type I vs . II fibres a higher β1 AMPK (+215%) and lower γ3 AMPK expression (−71%) was found. α1, α2, β2 and γ1 AMPK expression was similar between fibre types. In type I vs . II fibres phosphoregulation after CON was similar (AMPK Thr172, ACC Ser221, TBC1D1 Ser231 and GS 2+2a ) or lower (TBC1D4 Ser704 ). Following INT, phosphoregulation in type I vs . II fibres was lower (AMPK Thr172, TBC1D1 Ser231, TBC1D4 Ser704 and ACC Ser221 ) or higher (GS 2+2a ). Exercise‐induced glycogen degradation in type I vs . II fibres was similar (CON) or lower (INT). In conclusion, a differentiated response to exercise of metabolic signalling/effector proteins in human type I and II fibres was evident during interval exercise. This could be important for exercise type‐specific adaptations, i.e. insulin sensitivity and mitochondrial density, and highlights the potential for new discoveries when investigating fibre type‐specific signalling.